The Effect of Caffeine Consumption Habits and Sleep Quality on Hemoglobin Levels in Adolescent Girls - Nurrahma, Ari; Mustafa, Annasari; Wulandari, Lisa Purbawaning; Setyarini, Didien Ika (Health Access Journal, 2025)
Adolescent girls are particularly vulnerable to anemia as they undergo rapid growth during puberty, which increases their iron requirements to support this growth. Several factors contribute to the occurrence of anemia, including the habitual consumption of iron-inhibiting substances such as caffeine and poor sleep quality. This study aimed to investigate the effects of caffeine consumption habits and sleep quality on hemoglobin levels among adolescent girls aged 15-18 at SMAN 8 Malang. The research design was analytical with a cross-sectional method. The sampling technique used was two-stage clustering random sampling. Data collection involved the use of the SQ FFQ, PSQI questionnaires, and the Point Care of Testing (POCT) method for hemoglobin level analysis, which was analyzed using Spearman rank correlation and logistic regression tests. The results of the Spearman rank correlation test revealed a relationship between caffeine consumption habits and hemoglobin levels (p-value = 0.000 < 0.05), sleep quality and hemoglobin levels (p-value = 0.005 < 0.05), and no relationship between caffeine consumption and sleep quality (p-value = 0.646 > 0.05). The logistic regression test showed a significant effect of caffeine consumption habits and sleep quality on hemoglobin levels in adolescent girls (significant value 0.000 < 0.05).